Astronomical Measurement A Concise Guide - Lawrence, Andy (Astronomy and Planetary Sciences,, 2014)
This book on astronomical measurement takes a fresh approach to teaching the subject. After discussing some general principles, it follows the chain of measurement through atmosphere, imaging, detection, spectroscopy, timing, and hypothesis testing. The various wavelength regimes are covered in each section, emphasising what is the same, and what is different. The author concentrates on the physics of detection and the principles of measurement, aiming to make this logically coherent. The book is based on a short self contained lecture course for advanced undergraduate students developed and taught by the author over several years.